Ovine pulmonary adenocarcinoma diagnosis and control in practice. (2nd July 2020) - Hinde, Davinia; Evans, Mike; Scott, Phil
Abstract : This article discusses the diagnosis and control of ovine pulmonary adenocarcinoma (OPA), an 'iceberg disease' which can have both a large economic impact on flocks, and a damaging effect on the reputation of flocks supplying animals for breeding purposes. The potential control methods and their limitations are discussed, and two case studies illustrate how they have been applied by mixed practitioners working on commercial farms.